RESTORATION OF MOTOR FUNCTION AND POSTURAL BALANCE FOLLOWING BRAIN TUMOR SURGERY (Центральноазиатский журнал образования и инноваций, 2025)
Following neurosurgical procedures for brain tumors, patients frequently experience motor impairments such as decreased motor function, hemiparesis, balance disturbances, and reduced overall mobility. These issues are particularly common when tumors are located near the pyramidal tracts, basal ganglia, or motor activation centers (Stummer et al., 2008). Such impairments significantly reduce a patient’s independence in daily life, making early and comprehensive rehabilitation essential. In this study, 25 patients were enrolled in a four-month individualized rehabilitation program. Kinesiotherapy exercises based on the Bobath method and the Brunnstrom concept were employed. Motor functions were assessed using the Fugl-Meyer Assessment (FMA), Berg Balance Scale, and Timed Up and Go test (Gladstone et al., 2002). These tests helped evaluate the patients’ mobility, balance maintenance, and walking speed.